Java: A Beginner's Guide, Tenth Edition - Schildt, Herbert; Coward, Danny (McGraw-Hill/Osborne, 2024)
This proven guide delivers the appropriate mix of theory and practical coding necessary to get readers up and running developing their own Java applications from the ground up or customize existing code. --